(untitled) (Comprehensive Journal of Science, 2026)
The purpose of this study is to compare the average longitudinal thermal expansion coefficient α, surface β, and volumetric coefficient γ for three metals, namely aluminum, iron, and copper. The results of the study showed that: - The relationship between the change in temperature ∆T and the change in length ∆L is direct (linear), The highest value of the average elongation was for aluminum (0.015625 cm) and the lowest for iron (0.005125 cm). - The highest value of the average coefficient of longitudinal, surface and volumetric thermal expansion of aluminum metal. - The lowest value for the average coefficient of longitudinal, surface and volumetric thermal expansion for iron metal. Since the average value of elongation and the average coefficient of longitudinal, surface and volumetric thermal expansion of iron metal is the lowest, therefore iron metal is used in the manufacture of iron connections in buildings, bridges, railways and highways, where spaces are left between the connections to give room for expansion and contraction, and if this is not done, it can Buildings crack, bridges collapse, and railways buckle due to thermal expansion.